The synergistic effect of radical and non-radical processes on the dephosphorization of dimethoate by vacuum ultraviolet: The overlooked roles of singlet oxygen atom and high-energy excited state - Jialiang Liang; Jingke Wu; Pengfei Gan; Yudan Liu; Zhen, Peng; Yunyi Li; Zhiwei Zhao; Liu, Wen; Meiping Tong (Water Research, 2023)
Organophosphorus pesticides are extensively utilized worldwide, but their incomplete dephosphorization poses significant environmental risks. This study investigates the dephosphorization of dimethoate (DMT), a representative organophosphorus pesticide, using a vacuum ultraviolet system. Surprisingly, in addition to hydroxyl radicals (•OH), non-radical processes such as photoexcitation and singlet oxygen atoms (O(1D)) exert more significant effects on DMT dephosphorization. The degradation kinetics of DMT demonstrate a perfect linear correlation with the radical yield in both UV-based and VUV-based advanced oxidation processes (AOPs), with greater efficacy of radical attack observed in the VUV system. This heightened efficiency is attributed to the excitation of DMT to a high-energy excited state induced by UV185 radiation. Additionally, •OH alone is inadequate for achieving complete dephosphorization of DMT. The Fukui index and singly occupied orbital (SOMO) analysis reveal that the O(1D) generated by UV185-induced photolysis of O2 exhibits exceptional selectivity towards P=S bonds, thereby playing an indispensable role in the dephosphorization process of DMT. This study highlights the significant contribution of non-radical pathways in DMT dephosphorization by VUV, which holds great implications for the advancement of photochemical-based AOPs.
Keywords: Excited state; Non-radical processes; Singlet oxygen atom; Spin density; Transition state